How can we discover developable antibody-based biotherapeutics? - Bauer, Joschka; Rajagopal, Nandhini; Gupta, Priyanka; Gupta, Pankaj; Nixon, Andrew E.; Kumar, Sandeep (Frontiers in Molecular Biosciences, 2023)
Antibody-based biotherapeutics have emerged as a successful class of pharmaceuticals, despite significant challenges and risks to their discovery and development. This review discusses the most frequently encountered hurdles in research and development of antibody-based biotherapeutics and proposes a conceptual framework called Biopharmaceutical Informatics. Our vision advocates for the syncretic use of computation and experimentation at every stage of biologic drug discovery, considering developability (manufacturability, safety, efficacy, and pharmacology) of potential drug candidates from the earliest stages of the drug discovery phase. The computational advances in recent years allow for more precise formulation of disease concepts, rapid identification, and validation of targets suitable for therapeutic intervention, and discovery of potential biotherapeutics that can agonize or antagonize them. Furthermore, computational methods for de novo and epitope-specific antibody design are increasingly being developed, opening novel computationally driven opportunities for biologic drug discovery. Here, we review the opportunities and limitations of emerging computational approaches for optimizing antigens to generate robust immune responses, in-silico generation of antibody sequences, discovery of potential antibody binders through virtual screening, assessment of hits, identification of lead drug candidates, and their affinity maturation and optimization for developability. The adoption of Biopharmaceutical Informatics across all aspects of the drug discovery and development cycles should help bring affordable and effective biotherapeutics to patients more quickly.